Edukasi Pola Hidup Aktif Bagi Lansia Supaya Bebas Hipertensi Di Desa Gumpang, Sukoharjo - Cencen Fauziah Banowati; Lilik Ariyanti; Muhammad Jofan Martin Audifa; Oktavia Putri Rahmadhani; Misael Valentino Gunawan; Zalika Lailahusna Haryanto (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Hypertension is a major non-communicable disease among older adults and a leading risk factor for cardiovascular disease. This community service activity aimed to improve older adults' knowledge of hypertension prevention and control through health education and hypertension exercise. The methods included interactive education, blood pressure measurement before and after the intervention, hypertension exercise, and pretest-posttest evaluation involving 14 older adults in Gumpang Village, Sukoharjo. The results showed a decrease in mean systolic blood pressure from 145.21 mmHg to 134.93 mmHg and diastolic blood pressure from 78.50 mmHg to 72.64 mmHg. The average pretest score was 95.0%, while all participants evaluated in the posttest answered all questions correctly (100%). Health education combined with hypertension exercise effectively improved knowledge and promoted an active lifestyle to support non-pharmacological hypertension control among older adults.